Penerapan Metode Operational Competitiveness Rating Analysis (OCRA) Dalam Penerimaan Karyawan Perjanjian Kerja Waktu Tertentu (PKWT) - Nona Oktari; Mesran Mesran; Dito Putro Utomo; Soeb Aripin; Abdul Karim (Journal of Information System Research (JOSH), 2022)
Certain Employment Agreement Employees (PKWT) or can also be referred to as contract employees in a company who are hired to help work within the company, but it is not certain how it is implemented based on only being a temporary employee. In a sense, after it expires, the company can extend or lift the contract as a permanent employee, by looking at how active the employee is. In the process of selecting PKWT employees, the company must obtain prospective applicants objectively so that the results match the desired criteria. In the process of hiring PKWT employees there are problems, namely because of the large number of candidates so that it takes a long time to select them. The next problem is that the selection process still looks inefficient and takes time, because the assessment and results of PKWT implementation are carried out in stages, such as file selection, interviews and so on. Thus, it is likely that errors in the final result of anticipating PKWT employees often do not meet the criteria required by the company and hinder the company's performance. Therefore, a Decision Support System (SPK) is needed to overcome the problems that occur in the acceptance of Specific Time Agreement Employees (PKWT) using the OCRA method. The OCRA method is one of the methods of the Decision Support System, where this method makes decisions by ranking from the smallest value to the largest value. With this system, it is expected to be able to obtain optimal system decisions and can minimize the performance of the company in the process of accepting Employees of Specific Time Work Agreements (PKWT).